2000
DOI: 10.1348/096317900167182
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial job strain and productivity in human service workers: A test of the demand‐control‐support model

Abstract: The aim of the study was to test the main and interactive eVects of the key dimensions of the demand-control-support model in predicting levels of strain (speci cally emotional exhaustion, depersonalization and job dissatisfaction) and feelings of productivity and competency (personal accomplishment) in a multioccupational sample of human service workers (N = 813). Controlling for demographics, negative aVectivity (NA), and quadratic terms, structural equation analyses showed some support for the additive iso-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
103
0
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(118 citation statements)
references
References 41 publications
9
103
0
6
Order By: Relevance
“…Consistent with this reasoning, Demerouti et al (2001) and Dollard et al (2000) reported that jobs combining high demands with high control produced the highest levels of personal accomplishment (a subscale of the Maslach Burnout Inventory (Maslach and Jackson, 1986) that reflects feelings of competence and successful achievement in one's work). In a carefully designed study, Parker and Sprigg (1999) found main effects of job control and job demands on perceived mastery (a measure tapping whether one felt able to resolve selected job-related problems) and role breadth self-efficacy (a concept reflecting one's confidence regarding carrying out a range of proactive or interpersonal tasks).…”
Section: Active Learning: What Do We Know?mentioning
confidence: 75%
See 2 more Smart Citations
“…Consistent with this reasoning, Demerouti et al (2001) and Dollard et al (2000) reported that jobs combining high demands with high control produced the highest levels of personal accomplishment (a subscale of the Maslach Burnout Inventory (Maslach and Jackson, 1986) that reflects feelings of competence and successful achievement in one's work). In a carefully designed study, Parker and Sprigg (1999) found main effects of job control and job demands on perceived mastery (a measure tapping whether one felt able to resolve selected job-related problems) and role breadth self-efficacy (a concept reflecting one's confidence regarding carrying out a range of proactive or interpersonal tasks).…”
Section: Active Learning: What Do We Know?mentioning
confidence: 75%
“…De Jonge, Van Breukelen, Landeweerd & Nijhuis (1999), De Jonge, Dollard, Dormann, Le Blanc & Houtman (2000 and Dollard, Winefield, Winefield & De Jonge (2000) found in three studies among health care and human service workers that active jobs produced the highest levels of job satisfaction. The results of two other studies are not entirely consistent with the learning hypothesis.…”
Section: Active Learning: What Do We Know?mentioning
confidence: 98%
See 1 more Smart Citation
“…But too much of a good thing is not necessarily a good thing. It can lead to burnout, high levels of dysfunctional stress, and emotional exhaustion (Dollard, Winefield, Winfield & Jonge, 2000;Xie & Johns, 1995), as well as to the loss of non-work identity (Rouseeau & Arthur, 1999). How, then, do C-bAEs' participants keep from becoming their own worst enemies?…”
Section: Work Loadmentioning
confidence: 99%
“…Podrška od strane kolega se odnosi na to koliko su zaposleni prijateljski nastrojeni i podržavajući, dok se podrška od nadređenih odnosi na to koliko oni ohrabruju svoje zaposlene da podržavaju jedni druge (Dollard, Winefield, Winefield, & de Jonge, 2000). Sa jedne strane, prisustvo kolega koji podržavaju i dobijanje povratnih informacija od nadređenog povećavaju verovatnoću da će se postići radni ciljevi (Schaufeli & Bakker, 2004).…”
unclassified